Transformasi Media Digital dalam Katekese Kontekstual: Studi Kasus terhadap Pengelolaan Pelayanan Gereja-Gereja Kontemporer - Agnes Dwi Rahayu; Intansakti Pius X (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
In the ever-evolving digital age, the transformation of digital media affects church ministry management and contextual catechesis. This article explores the ministry management of contemporary churches in facing challenges and opportunities due to advances in digital technology, especially in the context of catechesis. The church faces major changes in the delivery of the gospel message and Christian values to the people, seeing the transformation of digital media as both a challenge and an opportunity to increase the relevance and complexity of the church's outlook in the digital age. The main challenge is to integrate the concept of contextual catechesis with technological developments. Although digital transformation opens up opportunities for online catechesis, churches must ensure that evangelical messages remain relevant and understood by the people. The ministry management strategy of contemporary churches involves improving the accessibility and quality of services through digital technology. Engaging and interactive catechetical content is developed for more effective ministry. This study emphasizes the importance of involving people in decision-making and service delivery as the key to optimizing the potential of digital media transformation. By responding to the changing times, contemporary churches can utilize digital technology to expand the reach of the evangelical message and enhance ministry effectiveness, providing opportunities to respond to the needs of the people in a changing era.